Comparison of risk factors for four sexually transmitted infections: results from a study of attenders at three genitourinary medicine clinics in England. Issue 4 (1st August 2000) - Hughes, G; Catchpole, M; Rogers, P A; Brady, A R; Kinghorn, G; Mercey, D; Thin, N
Abstract : Objective: To compare the risk factors for four common sexually transmitted infections (STIs) in attenders at three large urban genitourinary medicine (GUM) clinics in England. Methods: Clinical, demographic, and behavioural data on attenders at two clinics in London and one in Sheffield were collected. Risk factors associated with first episodes of genital warts and genital herpes simplex virus (HSV), and uncomplicated gonorrhoea and chlamydia were investigated using the presence of each of these STIs as the outcome variable in separate multiple logistic regression analyses. Results: Using data on the first attendance of the 18 238 patients attending the clinics in 1996, the risk of a gonorrhoea or chlamydia diagnosis was strongly associated with teenagers compared with those aged over 34, with black Caribbeans and black Africans compared with whites, and increased with the number of sexual partners. The risk of genital warts or HSV diagnosis was lowest in black Caribbeans and black Africans compared with whites and was not associated with the number of sexual partners. While genital warts were associated with younger age, odds ratios were much lower compared with those for the bacterial infections. Genital HSV diagnoses were not associated with age. Conclusions: This study of GUM clinic attenders suggests a reduction in the incidence of bacterial STIs may be achievable through targeted sexual health promotion focusing particularly on black ethnic minorities, teenagers, and those with multiple sexual partnerships. Viral STIs were less clearly associated with population subgroups and a broader population based approach to sexual health promotion may be more effective in controlling these infections.